2021
DOI: 10.3390/foods10020347
|View full text |Cite
|
Sign up to set email alerts
|

Use of DNA Barcoding Combined with PCR-SFLP to Authenticate Species in Bison Meat Products

Abstract: American bison (Bison bison) meat is susceptible to species mislabeling due to its high value and similar appearance to meat from domestic cattle (Bos taurus). DNA barcoding is commonly used to identify animal species. However, as a result of the historical hybridization of American bison and domestic cattle, additional genetic testing is required for species confirmation. The objective of this study was to perform a market survey of bison meat products and verify the species using DNA barcoding combined with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…(2018), and Scales et al. (2021) applied DNA barcoding techniques to screen various game meat products (burger patties, ground beef, hot dogs, sausages) purchased from stores, retail outlets, and online vendors. The general working principle used by this technique involves amplification of the ∼650‐bp fragment of the mitochondrial gene encoding cytochrome c oxidase subunit I (COI).…”
Section: Dna‐based Methods For Game Species Identificationmentioning
confidence: 99%
See 3 more Smart Citations
“…(2018), and Scales et al. (2021) applied DNA barcoding techniques to screen various game meat products (burger patties, ground beef, hot dogs, sausages) purchased from stores, retail outlets, and online vendors. The general working principle used by this technique involves amplification of the ∼650‐bp fragment of the mitochondrial gene encoding cytochrome c oxidase subunit I (COI).…”
Section: Dna‐based Methods For Game Species Identificationmentioning
confidence: 99%
“…He et al (2018) confirmed the cheapness and simplicity of the restriction fragment length assay in their work authenticating pigeon and quail meat products. PCR-SFLP (satellite fragment length polymorphism), another variant of PCR-RFLP, was used in a study that confirmed the presence of other species in bison meat products (Scales et al, 2021). This method was used to further increase the specificity of the DNA barcoding result that identified three samples of 45 tested products as domestic cattle.…”
Section: Polymerase Chain Reaction-restriction Fragment Length Polymo...mentioning
confidence: 99%
See 2 more Smart Citations